The Impact of Digitalization on the Sustainable Development of Ukraine: COVID-19 and War Challenges for Higher Education - Marhasova, V.; Kholiavko, N.; Popelo, O.; Krylov, D.; Zhavoronok, А.; Biliaze, O. (Revista de la Universidad del Zulia, 2023)
Higher Education plays an important role in ensuring the Sustainable Development of the countries.The purpose of the article is to systematize scientific approaches to the study of the impact of digitalization on ensuring the Sustainable Development of Ukraine and its regions in the conditions of modern COVID-19 and military challenges. The methodological basis of this study is a systematic approach, as well as general and special scientificresearch methods, namely: systematic analysis and generalization, grouping, induction and deduction, abstract-logical, scientific abstraction and modeling, graphic methods.The authors verified that Higher Education has a tangible positive impact on the dynamics of Sustainable Development of Ukraine and its regions. First of all, this influence is carried out through the educational and research activities of universities. The article emphasizes that it was digitalization that allowed universities to maintain their competitive positions in the educational services market in the conditions of COVID-19 and war challenges
Keywords: Higher Education, universities, Sustainable Development, digitalization, informationtechnologies, COVID-19, war challenges